2022
DOI: 10.1021/acsnano.2c01543
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic All-Frame-Faceted Octahedral Nanoframes with Eight Engraved Y-Shaped Hot Zones

Abstract: We report the synthesis of all-frame-faceted octahedral nanoframes containing eight Y-shaped hot zones in a single entity where electromagnetic near-field focusing can be maximized. To realize such state-of-the-art complex nanoframes, a series of multiple stepwise bottom-up processes were executed by exploiting Au octahedral nanoparticles as the initial template. By rationally controlling the chemical reactivity of different surface facets (i.e., vertexes, edges, and terraces), the Au octahedral nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…2,51,52 By mirroring a strategy used in photolithography, we have reported a bottom-up nanopatterning method for all-frame-faceted octahedral NFs where Pt tripod NFs were patterned on every facet of eight octahedral NPs (Figure 7a). 53 The critical step for the Y-shape-engraved octahedral NFs is to pattern the eight faces (i.e., (111) facets) of Au octahedral NPs to have 24 curved edge lines, which we call "chemical carving". 5 Such a complicated engraving process can be achieved by precisely tuning the electrochemical potential of a solution (E chem ) through a combination of experimental parameters such as temperature, pH, reducing agent, and surfactant concentration.…”
Section: Chemical Carvingmentioning
confidence: 99%
“…2,51,52 By mirroring a strategy used in photolithography, we have reported a bottom-up nanopatterning method for all-frame-faceted octahedral NFs where Pt tripod NFs were patterned on every facet of eight octahedral NPs (Figure 7a). 53 The critical step for the Y-shape-engraved octahedral NFs is to pattern the eight faces (i.e., (111) facets) of Au octahedral NPs to have 24 curved edge lines, which we call "chemical carving". 5 Such a complicated engraving process can be achieved by precisely tuning the electrochemical potential of a solution (E chem ) through a combination of experimental parameters such as temperature, pH, reducing agent, and surfactant concentration.…”
Section: Chemical Carvingmentioning
confidence: 99%
“…The strategies for designing advanced plasmonically intricate nanoreactors require a certain degree of morphological uniqueness so that they are able to harvest the maximum amount of light energy. 47,48 Several studies on the morphological modulation of plasmonic nanoparticles have shown that the localized surface plasmon resonance (LSPR) depends on the size and shape of the NCs. For instance, LSPR can be amplified significantly in the case of anisotropic nanostructures (i.e., cubes, prisms, and stars) compared with isotropic ones (i.e., spheres).…”
Section: Generation Of Plasmonic Hotspotsmentioning
confidence: 99%
“…[ 1,2 ] This phenomenon has been validated on various nanomaterials, including gold nanomaterials, [ 3,4 ] silver nanomaterials, [ 5,6 ] carbon nanomaterials, [ 7 ] and bimetallic nanomaterials. [ 8 ] Among all those nanomaterials, gold nanomaterials have been the center of interest in terms of their morphology and properties. [ 9,10 ] The photothermal effect, catalytic activity, and plasmonic activity of gold nanomaterials were proved to be highly dependent on their geometry and size.…”
Section: Introductionmentioning
confidence: 99%